Inhibition of autophagy enhances apoptosis induced by proteasome inhibitor bortezomib in human glioblastoma U87 and U251 cells - Zhang, Xudong (Springer US, 2013)
Glioblastoma is the most aggressive cerebral gliomas. Despite advances in therapies, the prognosis is still very poor. Therefore, novel therapeutic strategies are required. As a proteasome inhibitor, bortezomib has shown its efficacy as an active antitumor agent against a variety of tumors. However, inhibition of proteasome activity leads to cell death and also induces cell autophagy, and due to the dual roles of autophagy in the survival and death of tumor cells, the effect of inhibition of autophagy on glioblastoma cells remains to be explored. We therefore assessed whether bortezomib is capable of inducing autophagy, and investigated the antitumor effect of bortezomib combined with autophagy inhibitors on human glioblastoma U251 and U87 cells. Cell viability was measured by MTT assay. The expressions of autophagy and apoptosis-related proteins were determined by Western blot analysis. U251 and U87 cells proliferation was inhibited in a dose-dependent manner. Both apoptosis and autophagy induced by bortezomib were observed in human glioblastoma U87 and U251 cells. However, when U251 and U87 cells were co-treated with bortezomib and autophagy inhibitors 3-MA or Atg7 siRNA, the autophagy inhibitors blocked the autophagy in the cells and resulted in a further inhibition of cell proliferation and a further increase in cell apoptosis as compared with that treated with bortezomib alone. These findings indicated that combination of bortezomib and autophagy inhibitors may shed new light on glioblastoma treatment.